Die stöhnende Schöpfung in Röm 8,18-23: hermeneutische Überlegungen zur ethischen Orientierung in der heutigen Umweltkrise - Mader, Heidrun E. (Kerygma und Dogma, 2023)
In his letter to the Romans, Paul personifies creation as a woman groaning in labour pains (Rom 8:18-23). In contrast to Paul's image, Roman imperial propaganda presents creation in a paradisiacal state, personified as the goddess Tellus. For our present crisis-ridden perception of creation, Rom 8:18-23 is a powerful text on creation, aptly reflecting the present situation and appealing to human beings, themselves part of creation, to take responsibility for it in the context of a salvific relationship with their Creator. The new creation toward which the woman of Rom 8 is laboring, is more prevalent in New Testament texts than the present creation. Yet, the new creation does not acquit humans of their responsibility for the hic et nunc, but functions as a model for attending to the present creation.